Sandpaper nails: an uncommon tale of twenty-nail dystrophy in a 5-year-old - S. S., Nandagopal; George, Jewel Maria; Cherian, Carol Sara; Abraham, Jacob (International Journal of Contemporary Pediatrics, 2025)
Trachyonychia, also known as twenty-nail dystrophy (TND), is a rare nail matrix disorder in children, often idiopathic but occasionally linked to dermatologic or immunologic conditions. Characterized by brittle, ridged, and roughened nails, it may coexist with systemic or cutaneous manifestations. We present the case of a 5-year-old girl admitted for fever and myositis, with a background of recurrent respiratory tract infections. On examination, she was found to have TND, patchy alopecia, dry skin, and bilateral medial madarosis-features suggestive of atopy. Anthropometric assessment indicated undernutrition. Her immunologic profile revealed significantly reduced serum IgA levels, with other immunoglobulins within normal range. Workup for autoimmune and malabsorptive conditions was negative. Dermatological consultation confirmed trachyonychia, and topical JAK inhibitor (Tofacitinib) was prescribed. Supportive care and close follow-up were advised. This case highlights a rare pediatric presentation of trachyonychia associated with features of atopy and selective IgA deficiency. The findings raise the possibility of an immunologic basis for TND in some children. Awareness of such associations can facilitate early diagnosis, comprehensive evaluation, and individualized management strategies in affected patients.